Effect of dose and types of the water reducing admixtures and superplasticizers on concrete strength and durability behaviour: a review - Wang, Xiao-Hui; Fang, Zhi-Chao; Zheng, Li (Journal of Civil Engineering and Management, 2024)
As one of the concrete admixtures, water reducing admixtures and superplasticizers are usually used to reduce the mixing water volume and improve the performance of the harden concrete while maintaining better workability of the fresh concrete. However, the concrete strength and durability properties are affected differently by different types and dosages of the water reducing admixtures and superplasticizers. Based on the published literatures, this paper comprehensively reviews and analyzes this problem. Different types of the concretes, including ordinary Portland cement concrete, ordinary Portland cement concrete containing pozzolan, fly ash and ground granulated blast furnace slag, calcium sulfoaluminate cement concrete, ferrite aluminate cement concrete, recycled aggregates concrete, lightweight aggregate concrete, self-compacting concrete and ultra-high performance concrete, are considered to discuss the influence of types and dosages of the water reducing admixtures and superplasticizers on their strengths. Water absorption, frost resistance and permeability resistance of the concrete are mainly reviewed to discuss this influence on the durability properties of the concrete. Then, some suggestions on the application of the water reducing admixtures and superplasticizers in reinforced concrete structures and projects are proposed.